The Relationship between MCMI Personality Types and Social Anxiety Disorder in Universitas Airlangga Medical Students Class of 2019 - Robbani, Shafa Safira; Margarita Maria Maramis; Reny I’tishom; Erikavitri Yulianti (Jurnal Psikiatri Surabaya, 2026)
Introduction: Social Anxiety Disorder (SAD) is one of the most common forms of anxiety. SAD typically begins in late adolescence and is the cause of low self-esteem. This study aimed to investigate the unidentified cause of Social Anxiety Disorder (SAD), namely personality type as determined by the MCMI. Methods: This study was conducted on a sample of 148 respondents, who are the medical students at the Faculty of Medicine, Universitas Airlangga, year 2019. All of the respondents were required to fill out two questionnaires, the Millon Clinical Multiaxial Inventory IV (MCMI-IV) for identifying respondents’ personality type and the Liebowitz Social Anxiety Scale (LSAS) for measuring respondents’ social anxiety scale. All data was analysed using a non-parametric test in SPSS 16. Results: The result of this test indicates that there is a significant correlation between one of the narcissistic personality domains, which is admirable self-image, and the presence of SAD. Conclusions: In conclusion, there is no correlation between personality types based on MCMI and SAD. Nevertheless, admirable self-image, which is one of the domains of narcissistic personality, has a significant correlation with SAD.